2021
DOI: 10.1002/mgg3.1707
|View full text |Cite
|
Sign up to set email alerts
|

In silico modeling of the interaction between TEX19 and LIRE1, and analysis of TEX19 gene missense SNPs

Abstract: Background Testis expressed 19 (TEX19) is a specific human stem cell gene identified as cancer‐testis antigen (CTA), which emerged as a potential therapeutic drug target. TEX19.1, a mouse paralog of human TEX19, can interact with LINE‐1 retrotransposable element ORF1 protein (LIRE1) and subsequently restrict mobilization of LINE‐1 elements in the genome. Aim This study aimed to predict the interaction of TEX19 with LIRE1 and analyze TEX19 missense polymorphisms. TEX19 model was generated using I‐TASSER and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The major causes of IDA in Saudi Arabia include inadequate consumption of Vitamin C, infrequent consumption of red meat and fish, and genetic/or family history of IDA [ 8 , 10 ]. Several polymorphisms have been previously reported in the Saudi population as causative single nucleotide polymorphisms (SNPs) in diseases such as breast cancer [ 12 16 ], colon cancer [ 17 19 ], diffuse parenchymal lung disease [ 20 ], and acute myeloid leukemia [ 21 , 22 ]. In addition, genetic risk factors for IDA and causative genes have also been identified including the TMPRSS6 gene [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major causes of IDA in Saudi Arabia include inadequate consumption of Vitamin C, infrequent consumption of red meat and fish, and genetic/or family history of IDA [ 8 , 10 ]. Several polymorphisms have been previously reported in the Saudi population as causative single nucleotide polymorphisms (SNPs) in diseases such as breast cancer [ 12 16 ], colon cancer [ 17 19 ], diffuse parenchymal lung disease [ 20 ], and acute myeloid leukemia [ 21 , 22 ]. In addition, genetic risk factors for IDA and causative genes have also been identified including the TMPRSS6 gene [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To comprehend the pathogenesis and create a treatment plan, it is essential to identify the genetic and hereditary factors [51]. Numerous genes, including PALB2, ATM, BARD1, BRCA1, BRCA2, and CHEK2, have significantly maintained DNA fidelity and genomic integrity [52][53][54]. They are also essential in controlling the HR mechanics.…”
Section: Breast Cancer Mutationsmentioning
confidence: 99%
“…Recently, genetic factors have been identified that may play an essential role in the pathogenesis of IDA [23]. Several polymorphisms have been previously reported in the Saudi population as causative Single Nucleotide Polymorphisms (SNPs) in diseases such as breast cancer [24], colon cancer [25], diffuse parenchymal lung disease [19] [26], and acute myeloid leukemia [24]. In addition, genetic risk factors for IDA and causative genes have also been identified including the TMPRSS6 gene [26].…”
Section: Introductionmentioning
confidence: 99%